Treatment of Textile Wastewater with Chlorine: An Effective Method (Chemical Engineering Research Bulletin, 2010)
As the chlorination of textile wastewater achieves all the objectives of its treatment such as color removal and reduction of TDS, BOD and COD; and the treated effluents meet the standards set as per Schedule 12-B of the Environment Conservation Rules-1997 (ECR-97, Bangladesh), the treatment of textile wastewater with chlorine gas is a practical technological option for Bangladesh. If this process which is simple if adopted by the textile sector, the ETP operation would be widely practised for its low operating costs because of low price of chlorine produced by local chlor-alkali plants in the country. Satisfactory operation of the ETPs treating textile wastewater with chlorine at low costs has made this process affordable and attractive to the textile sector. Some of the perceived limitations of chlorination outweighs the greater benefits of textile wastewater treatment with chlorine gas leading to cleaner water bodies which receive these effluents otherwise.Keywords:Textile wastewater, chlorination, ETP, wastewater treatmentDOI = 10.3329/cerb.v14i1.3206 Chemical Engineering Research Bulletin 14 (2010) 59-63